2017
DOI: 10.4999/uhod.171668
|View full text |Cite
|
Sign up to set email alerts
|

Association Between PON1 L55M Polymorphism and PON1 Enzyme Activity in Patients with Leukemia.

Abstract: Paraoxonase 1 (PON1) is an important antioxidant enzyme which has a role in preventing the effects of systemic oxidative stress. The purpose of our study was to investigate the possible association between PON1 L55M polymorphism and leukemia development and to determine the relationship between PON1 genotypes and PON1 enzyme activities. Genotypes of 102 cases and 112 healthy controls were determined by PCR-RFLP. PON1 enzyme activity was determined according to Eckerson's method. The ratio of MM genotype belong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…These individuals participated in a previously published case-control study. The cases and controls have been described previously in terms of data collection and study procedures [26]. This study has the approval of the Ethics Committee, Faculty of Medicine, The University of Mersin.…”
Section: Patients and Tissue Samplesmentioning
confidence: 99%
“…These individuals participated in a previously published case-control study. The cases and controls have been described previously in terms of data collection and study procedures [26]. This study has the approval of the Ethics Committee, Faculty of Medicine, The University of Mersin.…”
Section: Patients and Tissue Samplesmentioning
confidence: 99%
“…Variations due to the presence of single nucleotide polymorphisms in antioxidant enzyme genes may contribute to the interindividual differences of transcript levels and enzyme activities, which might play a significant role in the prostate cancer development [14,22]. Therefore, the aim of the present study was to investigate the relation between PON1 L55M, Q192R and I102V polymorphisms and prostate can-cer risk in Polish men.…”
Section: Introductionmentioning
confidence: 97%
“…It was suggested that PON1 55M allele could correlate with higher PON1 activity than PON1 55L allele. In another study, it was observed that the differences in the PON1 serum levels linked to the L55M polymorphism were due to the reduced stability of the PON1 55M protein [22]. The hydrolyzing activity of the protein encoded by the 192RR, second the most common genotype of PON1 gene, is 8-fold higher than that encoded by the 192QQ.…”
Section: Introductionmentioning
confidence: 99%